Mobile thrombi in three chambers of the heart - Rachel Kunkler; David Scott Weisman; Ijaz Khan (Greater Baltimore Medical Center, 2013)
A case report of pulmonary embolus complicated by mobile thrombus in three chambers of the heart with emphasis on treatment and management options.